1983
DOI: 10.1099/00221287-129-2-431
|View full text |Cite
|
Sign up to set email alerts
|

Virulence For Mice Of A Proteinase-Secreting Strain Of Candida Albicans And A Proteinase-Deficient Mutant

Abstract: A proteinase-deficient mutant of Candida albicans, M 12, was produced by nitrosoguanidine mutagenesis of a proteinase-producing strain, ATCC 28366. The mutant was phenotypically identical to its parent in nearly all biochemical and morphological characteristics except proteinase production. The mutant was considerably less lethal than the parent when inoculated intravenously into mice and lower counts of C. albicans were recovered from the organs of mice infected with the mutant. Both strains were phagocytosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
0
3

Year Published

1984
1984
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(125 citation statements)
references
References 21 publications
5
117
0
3
Order By: Relevance
“…The secretion of hydrolases and production of hyphae have frequently been cited as determinants of virulence in C. albicans (Odds, 1979). Recently MacDonald & Odds (1983) reported the isolation of a protease-secretion-deficient mutant of C. albicans which was less virulent towards mice. Although mycelium is usually encountered in infected tissue the importance of hyphae in the development of candidosis has remained controversial (Odds, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The secretion of hydrolases and production of hyphae have frequently been cited as determinants of virulence in C. albicans (Odds, 1979). Recently MacDonald & Odds (1983) reported the isolation of a protease-secretion-deficient mutant of C. albicans which was less virulent towards mice. Although mycelium is usually encountered in infected tissue the importance of hyphae in the development of candidosis has remained controversial (Odds, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Staib (1969) reported that proteinase-positive (Prt+) strains of C. albicans were virulent in experimental murine infections whereas proteinase-negative (Prt-) isolates were avirulent. Macdonald & Odds (1983) found that a proteinase-deficient mutant, less virulent than its Prt+ parent in mice infections, was phagocytosed and killed by human and murine polymorphonuclear leukocytes to a greater extent than its Prt+ parent when both strains were grown in proteinase-inducing medium. The finding that mutants of C. albicans lacking extracellular proteinase were less virulent was corroborated by Kwon-Chung et al (1985).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical isolates from patients with acute pseudomembranous candidiasis and denture stomatitis were highly lethal to mice regardless of proteinase activity. In other experiments by us and others the proteinase-deficient mutant had no lethal effect on mice4, 13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for acid proteinase as a virulence factor may be considered to be invasion of keratinized skin by C. albicans and correlation with adherence of the organism940). However, evidence against proteinase as a virulence factor has also been reported1, 14,15). The present study indicates that the yeast forms of the clinical isolates, though having various degrees of proteinase activity, were more virulent for mice than the germ tube-forming cells, and that proteinase activity of C. albicans isolated from patients with dental caries and xerostomia is correlated with virulence for mice.…”
Section: Discussionmentioning
confidence: 99%